Teknik Memanggil Kaum Milenial (TMKM) untuk Modul Optimasi menggunakan Linear Programing dengan Excel Solver - Inderawati, Maria Magdalena Wahyuni; Hidayat, Trifenaus Prabu; Sugioko, Andre; Wong, Felicitas; Surya, Andre; Mekel, Bianca; Milano, Yosephan (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2023)
Optimization is the search for the optimal value of a problem with the help of one or more objective functions. Optimization problems are often found in everyday life and become important in the operation of a production system. The simplest optimization problem in the industrial world is solved using linear programming. Linear programming equations are made to solve optimization problems in the industrial world. In optimizing a problem, computational tools are needed to produce the optimal solution. Many computational tools are used, one of which is Excel Solver. Excel Solver is operated because many Microsoft Office users have this computing tool. Where everyone commonly uses Excel. The world of industrial Engineering needs someone who can solve optimization problems, especially since the current industrial era is getting more advanced. More skills are necessary for dealing with the Industrial Revolution 4.0 and Society 5.0, and it becomes a mandatory ability for an industrial engineer to solve this problem. Therefore, this community service activity is proposed with the topic: